Screening and Process Optimization of Hybrid Probiotics for Fermented Potato Juice - Yuwei JIAO; Zhaoting DOU; Shuo TIAN; Min LIU; Haitian FANG (Shipin gongye ke-ji)
Concentrated juice was the remaining material liquid after the production of potato oral liquid, which itself contained rich nutrients. In order to enhance the health function of concentrated juice, four strains of probiotics were selected for fermentation using concentrated juice as raw material. After single strain fermentation experiment, Lactobacillus plantarum A, Lactobacillus plantarum B and Lactobacillus paracei suitable for concentrated juice fermentation were obtained by acid production efficiency and viable bacteria number as indicators, and then compounded, and the compound probiotics fermentation process of potato concentrated juice was optimized by using viable bacteria number and sensory score as indicators. The results showed that the optimum compound probiotics fermentation conditions of concentrated juice were as follows: fermentation temperature 37 ℃, inoculum size 1.5‰, fermentation time 12 h, strain combination ratio 1:1:2. Under these conditions, the viable bacteria number in the compound probiotics fermentation of potato concentrated juice could reach 12.63×108 CFU/mL, and sensory score was 81.7 points.